The Influence of Brand Image and Brand Trust on Interest in Buying Airline Tickets on the Tiket.Com Online Site - Doris Fadela Naurin (PT FORMOSA CENDEKIA GLOBAL, 2023)
The spread of digitalization to various levels of society, especially in Indonesia, has encouraged the emergence of many new digital-based types, namely the emergence of online sales sites or e-commerce.Tiket.com is an e-commerce site that sells train and airplane tickets, hotel reservations, and travel services. other. The purpose of this research is to find out how brand trust and image affect people's intention to buy airplane tickets from tiket.com. Quantitative methods are used in this research approach. 100 STTKD academics who bought airplane tickets online through tiket.com were the samples of this study. Utilizing the Purposive Sampling method to select the sample. As a research tool, questionnaires were distributed and checked for validity by testing the validity and reliability. Validity and reliability tests, multiple linear regression tests, simultaneous partial F and T tests, and the coefficient of determination (R2) were used in this analysis. The test results show that: 1) Brand image (X1) influences purchase intention (Y) with an interest value of 0.000 <0.05 and t count 0.000 <0.05. 2) With a significance value of 0.000 <0.05 and t count 0.000 0.05, brand trust (X2) has a positive and significant effect on purchase intention (Y). 3) With a significance value of 0.000<0.05 and a calculated f value of 0.000<0.05, brand image (X1) and brand trust (X2) simultaneously have a positive and significant effect on purchase intention (Y)